2020
DOI: 10.3390/ijerph17113963
|View full text |Cite
|
Sign up to set email alerts
|

Working Conditions in Social Firms and Health Promotion Interventions in Relation to Employees’ Health and Work-Related Outcomes—A Scoping Review

Abstract: Background: Social firms—a type of social enterprise—offer people with severe disabilities the possibility of employment and integration into the labor market. Since 01 January 2018, social firms in Germany are obligated to provide health promotion interventions for their employees. Therefore, the study aims to provide an overview of the current state of research on working conditions, coping strategies, work- and health-related outcomes, and health promotion interventions in social firms to derive recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
19

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(49 citation statements)
references
References 84 publications
2
28
0
19
Order By: Relevance
“…Qualitative themes suggest this may be accounted for by the generally supportive ethos of social firms, specifically atmospheres of openness and acceptance about mental health issues, flexibility, and strong peer and management support. There are similarities with the findings of other research on social firms, including both survey work [ 30 , 32 , 33 ] and smaller qualitative studies [ 35 38 , 46 ]. In particularly, the importance of social support, workplace accommodations, and an accepting working environment as defining features of social firms is highlighted internationally in this body of work.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Qualitative themes suggest this may be accounted for by the generally supportive ethos of social firms, specifically atmospheres of openness and acceptance about mental health issues, flexibility, and strong peer and management support. There are similarities with the findings of other research on social firms, including both survey work [ 30 , 32 , 33 ] and smaller qualitative studies [ 35 38 , 46 ]. In particularly, the importance of social support, workplace accommodations, and an accepting working environment as defining features of social firms is highlighted internationally in this body of work.…”
Section: Discussionsupporting
confidence: 80%
“…While IPS has been the principal vocational rehabilitation model internationally, it implementation in the UK and elsewhere has been problematic, particularly in relation to employment sustainability [ 17 ]. Social firms provide a different vocational rehabilitation model in which longer job tenure appears to be related to a workplace culture where accommodations and support are central [ 32 , 33 ]. They can provide longer-term employment within a dynamic model of vocational rehabilitation that is valued by many.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another cross-sectional study of Canadian social firms reported that the average length of job in social enterprises in Quebec was 77.8 months and in social enterprises in Ontario was 66.5 months, both of which are substantially longer than the average of 8 months reported in IPS trials (58). Finally, a recent scoping review of social firms research reported that average job tenure of people with disabilities ranged from 15 months (median) to 7.3 years (mean), with seven studies reporting an average job tenure of over 5 years (59). While these studies were not able to confirm causation of better job tenure, it is suggested that the availability of workplace accommodations without specific disclosure is associated with job retention.…”
Section: Social Firmsmentioning
confidence: 91%
“…In social firms, different types of job resources were provided for employees [ 7 ], like social support [ 2 4 , 8 – 27 ], flexibility regarding work schedules, work tasks or pace of work [ 2 4 , 8 , 10 13 , 16 , 19 , 22 24 , 26 ], structured work tasks [ 2 , 3 , 8 , 10 13 , 19 23 , 25 – 27 ], different options for training like the gradually introduction of tasks or access to educational resources [ 4 , 11 , 16 , 19 , 25 ] and increased levels of job security [ 3 , 8 , 10 12 , 19 , 23 , 24 , 26 , 27 ]. One essential resource is personified by supervisors themselves promoting a supportive work environment [ 2 , 3 , 8 , 11 , 19 , 26 ].…”
Section: Introductionmentioning
confidence: 99%